Study on the interface damage of CRTS Ⅱ slab track under temperature load. (August 2020) - Li, Yang; Chen, Jinjie; Wang, Jianxi; Shi, Xianfeng; Chen, Long
Abstract: To investigate the interface damage between the track slabs and the Cement Asphalt (CA) mortar layer of China Railway Track System (CRTS) Ⅱ slab track, this study established a three-dimensional finite element model of the track, in which a cohesive zone model was incorporated to simulate the non-linear traction-separation behaviour of the interface. The parameters of the cohesive model were calibrated by experimental data. A damage parameter based on the relative displacement between the track slabs and the CA mortar layer was introduced to characterize the interface damage. Different interfacial properties and different degree of joint defect were taken into consideration in the model. The interface damage evolution and distribution were investigated under the combined action of temperature rise and positive temperature gradient in summer. Results show that the proposed model is capable of predicting the interfacial damage between the track slabs and the CA mortar layer. Under the combined action of temperature rise and positive temperature gradient, interface damage initiates in the middle if bond strength is small, and at the edge if bond strength is larger. The temperature rise at which interface damage initiates when the narrow joint is incomplete can be much lower than when the narrow joint is undamaged.